Evaluasi Kualitas Pencahayaan Pada Ruang Perkuliahan Gedung C Fakultas Teknik Universitas Riau - Ikhbal Havif JH; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Light illuminance in the classrooms is one of the important aspects for convenience in learning.. Poor level of illuminance can affect eye health. According to the National Standard of Indonesia SNI 03-6575-2001, the recommended illuminance level for classrooms is 250 lux. In this study measure the illuminance level at 19 classrooms of Building C Faculty of Engineering, University of Riau. From the results of measurements obtained the average illuminance in all classrooms is 123,13 lux,the highest illuminance is 141 lux at room 317 and the lowest illuminance is 103,4 lux at room 314. The average illuminance is not recommended illuminance level. Therefore the evaluation and recalculation of the number of luminaires in 19 classrooms. From the calculation result using the zonal cavity method for rooms 304, 305, 306, 307, 308, 309, 310,311,312,313,314,315, the number of luminaires required is 9 luminaires with 3 rows and 3 columns and for rooms 301, 302,303,316,317,318,319 obtained luminaire requirement of 9 luminaires 3 rows and 3 columns.Keywords: Standart illuminance in the classroom, luminaire, zonal cavity method